2008
DOI: 10.1128/mcb.02021-07
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Protein 4.1R, a Mature Centriole Protein, Disrupts Centrosomes, Alters Cell Cycle Progression, and Perturbs Mitotic Spindles and Anaphase

Abstract: Centrosomes nucleate and organize interphase microtubules and are instrumental in mitotic bipolar spindle assembly, ensuring orderly cell cycle progression with accurate chromosome segregation. We report that the multifunctional structural protein 4.1R localizes at centrosomes to distal/subdistal regions of mature centrioles in a cell cycle-dependent pattern. Significantly, 4.1R-specific depletion mediated by RNA interference perturbs subdistal appendage proteins ninein and outer dense fiber 2/cenexin at matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 75 publications
1
30
0
Order By: Relevance
“…Moreover, MTs growing close to the cortex in 4.1R-KD cells undergo fewer episodes of catastrophe, longer periods of growth and less time pausing and shortening, compared with control MTs. Although a defective MT nucleation from the centrosome could account for some of these effects, no reduction in MT nucleation has been observed in 4.1R-KD cells (Krauss et al, 2008). We therefore assume that the effects on the dynamic behavior of the MT network at the cell edge that we describe here are specifically due to a lack of 4.1R at the cell cortex.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, MTs growing close to the cortex in 4.1R-KD cells undergo fewer episodes of catastrophe, longer periods of growth and less time pausing and shortening, compared with control MTs. Although a defective MT nucleation from the centrosome could account for some of these effects, no reduction in MT nucleation has been observed in 4.1R-KD cells (Krauss et al, 2008). We therefore assume that the effects on the dynamic behavior of the MT network at the cell edge that we describe here are specifically due to a lack of 4.1R at the cell cortex.…”
Section: Discussionmentioning
confidence: 86%
“…Nucleolin could anchor microtubules directly or via other anchoring protein localizing at the mature centriole such as ninein 14 since nucleolin antibodies immunoprecipitated ninein, or through p150 glued , APC, FOP, CAP350 and EB1, [40][41][42] Kif3a, 43 nudel 44 or 4.1R-135. 45 Previous studies have shown the presence of extra centrosomes markers containing structure in mitotic cells silenced for nucleolin. 28,29 Thus, it was suggested that nucleolin may act as a negative regulator of centriole duplication as it is the case for B23, 46 p53, 47 cdk1, 48 BRCA1 49 and CDK5RAP2.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that 4.1R depletion causes microtubule disorganization in vitro and in intact cells (Krauss et al, 2002;Krauss et al, 2004;Krauss et al, 2008). We reasoned that 4.1R could have significant interactions at the nucleo-cytoskeletal interface affecting centrosome tethering and microtubules, particularly if 4.1R were functionally associated with emerin and lamin A.…”
Section: Increased Centrosome-nuclear Envelope Distance After 41r Dementioning
confidence: 99%
“…It was subsequently discovered, however, that nucleated cells express multiple 4.1R isoforms at several subcellular locations (De Carcer et al, 1995;Delhommeau et al, 2002;Krauss et al, 1997b;Krauss et al, 1997a). In nucleated cells, protein 4.1R not only organizes plasma-membrane-cytoskeletal microstructure, but, as we have previously shown, it is also integral to mitotic spindle and centrosome assembly and structure (Krauss et al, 2004;Krauss et al, 2008). Furthermore, we found that 4.1R epitopes in mammalian and Xenopus laevis nuclei are partially coincident with RNA splicing and/or transcription factories, DNA replication assemblies, nuclear pores and the nuclear periphery, and are largely coincident with nuclear anti-actin signals in nuclear matrix (Krauss et al, 2003;Krauss et al, 1997a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation